Hubungan Antara Gaya Belajar dan Keaktifan Belajar Matematika Terhadap Hasil Belajar Siswa - Fathiya Eka Putri; Fitrah Amelia; Yesi Gusmania (Edumatika : Jurnal Riset Pendidikan Matematika, 2019)
The purpose of this study was to determine the correlation learning styles and learning activeness towards students' mathematics learning outcomes. This study was a correlation study with all students of class VIII SMP II Luqman Al-Hakim Batam as the population, they were 154 students. The sampling technique uses a purposive sampling technique. The sample in this study was 62 students. The data collection method used was documentation and questionnaires. The instrument in this study used was test that was valid and reliable (r1 = 0.841 and r2 = 0.859). The results showed that there was a significant correlation learning styles and student mathematics learning outcomes; there was a significant correlation learning activeness towards student mathematics learning outcomes; and there was a significant correlation learning styles and active learning together towards students' mathematics learning outcomes.